Experimental validation of ADACOR holonic control system - Leitão, Paulo (2010)
In the last years, several manufacturing control architectures using emergent paradigms and technologies, such as multi-agent and holonic manufacturing systems, have been proposed to address the challenge of developing control systems capable of handling certain types of disturbances at the factory level. One of these holonic architectures is ADACOR, which integrates a set of paradigms and technologies for distributed manufacturing systems complemented by formal modelling techniques, to achieve a flexible and adaptive holonic/collaborative control architecture. The results obtained in the first experiments using the ADACOR architecture are presented in this paper, and also compared to the results produced by other control architectures. For this purpose a set of quantitative and qualitative parameters were measured, to evaluate static and dynamic performance of the control architectures.